Pengaruh Penerapan Sistem Informasi Akuntansi, Sistem Pengendalian Internal Pemerintah Dan Kompetensi Sdm Terhadap Kualitas Laporan Keuangan Pada Kepolisian Daerah Sumatera Utara - Joppie Immanuel Tarigan; Eka Nurmala Sari (Kajian Akuntansi, 2021)
This study aims to determine, test and analyze the effect of accounting information systems, government internal control systems, human resource competence on the quality of financial reports at the North Sumatra Regional Police. This research method uses descriptive qualitative using a survey approach. The data analysis used the Structural Equation Modeling Partial Least Square (SEM-PLS) approach. The results of the study found that: First, the accounting information system did not have a significant effect on the quality of financial reports at the North Sumatra Regional Police. Second, the government's internal control system does not have a significant effect on the quality of financial reports within the North Sumatra Regional Police. Third, the competence of human resources has a significant effect on the quality of financial reports within the North Sumatra Regional Police. Fourth, the accounting information system, the government internal control system, and the competence of human resources together (simultaneously) have an influence on the quality of financial reports at the North Sumatra Regional Police. In an effort to improve the quality of financial reports at the North Sumatra Regional Police, it is necessary to improve technology and information infrastructure related to the availability of facilities and infrastructure, furthermore the professionalism of employees and special leadership auditors within the North Sumatra Regional Police needs to be improved, one of which is the opportunity to participate in education and training.